Transcutaneous immunization via dissolving microneedles protects mice from lethal influenza H7N9 virus challenge. Issue 47 (8th November 2022) - Liu, Siqi; Yang, Guozhong; Li, Minghui; Sun, Fang; Li, Yufeng; Wang, Xiliang; Gao, Yunhua; Yang, Penghui
Abstract: Avian influenza H7N9 virus has first emerged in 2013 and since then has spread in China in five seasonal waves. In humans, influenza H7N9 virus infection is associated with a high fatality rate; thus, an effective vaccine for this virus is needed. In the present study, we evaluated the usefulness of dissolving microneedles (MNs) loaded with influenza H7N9 vaccine in terms of the dissolution time, insertion capacity, insertion depth, and structural integrity of H7N9 virus in vitro . Our in vitro results showed MNs dissolved within 6 mins. The depth of skin penetration was 270 µm. After coating with a matrix material solution, the H7N9 proteins were agglomerated. We detected the H7N9 delivery time and humoral immune response in vivo . In a mouse model, the antigen retention time was longer for MNs than for intramuscular (IM) injection. The humoral response showed that similar to IM administration, MN administration increased the levels of functional and systematic antibodies and protection against the live influenza A/Anhui/01/2013 virus (Ah01/H7N9). The protection level was determined by the analysis of pathological sections of infected lungs. MN and IM administration yielded results superior to those in the control group. Taken together, these findings demonstrate that the use of dissolving MNs to deliver influenza H7N9 vaccines is a promising immunization approach.